Adsorption and Kinetics Studies of Cr (VI) by Graphene Oxide and Reduced Graphene Oxide-Zinc Oxide Nanocomposite - Taiba Naseem; Fozia Bibi; Saira Arif; Muhammad Waseem; Sirajul Haq; Mohamad Nor Azra; Taavi Liblik; Ivar Zekker (Molecules, 2022)
In this work, graphene oxide (GO) and its reduced graphene oxide-zinc oxide nanocomposite (rGO-ZnO) was used for the removal of Cr (VI) from aqueous medium. By employing a variety of characterization techniques, morphological and structural properties of the adsorbents were determined. The adsorption study was done by varying concentration, temperature, pH, time, and amount of adsorbent. The results obtained confirmed that rGO-ZnO is a more economical and promising adsorbent for removing Cr (VI) as compared to GO. Kinetic study was also performed, which suggested that sorption of Cr (VI) follows the pseudo-first-order model. For equilibrium study, non-linear Langmuir was found a better fitted model than its linearized form. The maximum adsorption capacity calculated for GO and rGO-ZnO nanocomposite were 19.49 mg/g and 25.45 mg/g, respectively. Endothermic and spontaneous nature of adsorption was detected with positive values of ΔS (change in entropy), which reflects the structural changes happening at the liquid/solid interface.